Capillary Stamping of Functional Materials: Parallel Additive Substrate Patterning without Ink Depletion. Issue 5 (23rd December 2020) - Runge, Mercedes; Hübner, Hanna; Grimm, Alexander; Manoharan, Gririraj; Wieczorek, René; Philippi, Michael; Harneit, Wolfgang; Meyer, Carola; Enke, Dirk; Gallei, Markus; Steinhart, Martin
Abstract: Patterned substrates for optics, electronics, sensing, lab‐on‐chip technologies, bioanalytics, clinical diagnostics as well as translational and personalized medicine are typically prepared by additive substrate manufacturing including ballistic printing and microcontact printing. However, ballistic printing (e.g., ink jet and aerosol jet printing, laser‐induced forward transfer) involves serial pixel‐by‐pixel ink deposition. Parallel additive patterning by microcontact printing is performed with solid elastomeric stamps suffering from ink depletion after a few stamp‐substrate contacts. The throughput limitations of additive state‐of‐the art patterning thus arising may be overcome by capillary stamping –parallel additive substrate patterning without ink depletion by mesoporous silica stamps, which enable ink supply through the mesopores anytime during stamping. Thus, either arrays of substrate‐bound nanoparticles or colloidal nanodispersions of detached nanoparticles are accessible. Three types of model inks are processed: 1) drug solutions, 2) solutions containing metallopolymers and block copolymers as well as 3) nanodiamond suspensions representing colloidal nanoparticle inks. Thus, aqueous colloidal nanodispersions of stamped drug nanoparticles, regularly arranged ceramic nanoparticles by post‐stamping pyrolysis of stamped metallopolymeric precursor nanoparticles and regularly arranged nanodiamond nanoaggregates are obtained. Capillary stamping may overcome the throughput limitations of state‐of‐the‐art additive substrate manufacturing while a broad range of different inks can be processed. Abstract : Capillary stamping with mesoporous silica stamps is explored as additive substrate patterning technique overcoming ink depletion, which limits the use of solid elastomeric stamps in state‐of‐the‐art microcontact printing. Using selected model inks containing low‐molecular‐mass drugs, functional polymers or nanoparticles, nanoparticle arrays and nanodispersions of detached nanoparticles are obtained.